Modification of the Rheological properties of Baiji asphalt using a chemical system (sulfur: epoxy) - Ammar Hamdoun; Moafeq Rabeea (College of Education for Pure Sciences, 2018)
There is a growing need for the production of a certain types of asphaltic materials having a good rheological properties compared with the nonmodified asphaltic materials, thus many experiments were performed to prepare a modified asphalt that can be used in different fields. This study aimed to modifying asphalt with addition of (epoxy and hardener) according to three steps as follow:- 1.The modification of asphalt with different ratios from epoxy (without adding hardener) in the presence of 1%(Wt%) sulfur at 180ºc for (1 ,2 and 3)hrs. 2.The best sample was obtained from step(1)treated with different ratios of hardener at the same conditions. 3.The step(1)and(2)was repeat in the presence of 0.25%(Wt%) AlCl3 as the catalyst for this treatment and 1%(Wt%) sulfur at 180ºc for(1 , 2 and 3)hrs. From this work we obtained the asphaltic materials which can be used in paving and mastic according to the measuring of the (ductility,penetration and softening point).